Perspective of Virtual Exhibition during the COVID-19 pandemic - Finta Lissimia; Lutfi Prayogi (Department of Architecture Universitas Muhammadiyah Jakarta, 2022)
Virtual exhibitions are growing driven by physical restrictions during the COVID-19 pandemic. The exhibition of works that were previously more physical in nature, can be visited physically is slowly turning into an exhibition that is visited virtually. This change is uncomfortable for the community. For this reason, a study is needed on the impact of virtual exhibition visits on the community during the COVID-19 restrictions. This study aims to answer these problems and at the same time evaluate the progress of virtual exhibitions in the early days of the pandemic. Collecting data using an online questionnaire on 49 architecture students. The results of the questionnaire were analyzed using distribution and content analysis for open-ended questions. Exhibition content is the main focus. in a virtual exhibition. Other aspects to consider are virtual quality, exhibition perception, and execution. Restrictions cause boredom and stress. Virtual exhibitions can help overcome these feelings. Virtual exhibitions are not a substitute for physical exhibitions because people do not feel the need to refrain from visiting virtual exhibitions. Professionals feel motivated to visit any exhibition whether physical or virtual. So virtual exhibitions function like physical exhibitions, the only difference is the impression and experience that visitors get